Membangun Pemikiran Kritis Melalui Metode Membaca Kritis Karya Sastra - HD, Dharma Satrya; Yuliatin, Riyana Rizki; Dewi, Puspita; Rahman, Ummi Risti Ayuni (LPPM Universitas Bumigora, 2023)
Critical thinking has a pivotal role in enhancing the quality of thinking of humans. It is because it has impact on their quality of life. Consequently, encouraging and stimulating students is crucial in schools. This community service activity aims to eliciting the students’ critical thinking through critical reading method. Several steps were conducted in implementing this community service activity namely pretest, critical reading implementation, and posttest. The results of the activity show that critical reading pursue the students to more non-judgmental; therefore, they might be wiser to perceive differences. The students were encouraged to read deeply to the texts and interpret the story both explicitly and implicitly. The interpretation process is correlated by the phenomenon of society. Interpretation in literature works in more flexible that it depends on the knowledge and experiences of the readers. The students respect to the difference through the diversity of the interpretation. This activity is expected to be conducted continuously to drill students’ critical thinking.